2000
DOI: 10.1017/s000711450000177x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble polysaccharide and biomass of red microalgaPorphyridiumsp. alter intestinal morphology and reduce serum cholesterol in rats

Abstract: The present study investigated the effects of the red microalga Porphyridium sp. on gastrointestinal physiology and lipid metabolism in male Sprague-Dawley rats. Diets containing dietary fibre from pelleted red microalgal cells (biomass) or their sulfated polysaccharide, pectin or cellulose (control) were fed to rats for a period of 30 d. All three fibre-supplemented diets increased the length of both the small intestine and colon, with a significantly greater effect in rats fed the algal polysaccharide. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 39 publications
(31 reference statements)
6
61
0
1
Order By: Relevance
“…There are no published reports of P. purpureum-producing toxins. Further, few earlier reports on feeding of P. purpureum biomass in chickens and rats did not show any toxic signs (Ginzberg et al 2000;Dvir et al 2000). In addition, the quality of P. purpureum biomass was ensured by using potable water and closed LDPE bioreactors for cultivation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are no published reports of P. purpureum-producing toxins. Further, few earlier reports on feeding of P. purpureum biomass in chickens and rats did not show any toxic signs (Ginzberg et al 2000;Dvir et al 2000). In addition, the quality of P. purpureum biomass was ensured by using potable water and closed LDPE bioreactors for cultivation.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in the present study, a decrease in cholesterol and triglyceride levels of rats was observed. A number of recent studies have shown that algae possess a cholesterol and lipid-lowering ability and demonstrated the potential health benefits of incorporating algae or algal by-products into the diet (Belay 2002;Dvir et al 2000;Ginzberg et al 2000). Moreover, the minimum recommended dietary intake of n-3 PUFA as prescribed by WHO and FAO is 250 mg day −1 , while the American Heart Association has recommended up to 500 mg day −1 for a healthy adult (Lichtenstein et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), pharmacological (drug delivery matrix) and medicinal (antiviral, hypocholesterolemic, antithrombotic, immunomodulatory activities, etc.) applications [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…25 These polysaccharides could be used as hypocholesterolemic or antiviral agents, potential pharmacological effects are expected in immune modulatory and antithrombotic activities, another application was described as oral drug delivery matrix. [26][27][28][29] Elucidating the structure of a complex carbohydrate requires first its fragmentation into characteristic oligosaccharidic units. In the present paper, the polysaccharide from Porphyridium sp.…”
Section: Introductionmentioning
confidence: 99%